[tex]A=( \frac{2}{1*3}+ \frac{2}{3*5}+ \frac{2}{5*7}+...+ \frac{2}{2013*2015}): \frac{2014}{2015* 3^{2n+1}} [/tex]
[tex]A=2( \frac{1}{1*3}+ \frac{1}{3*5}+ \frac{1}{5*7}+...+ \frac{1}{2013*2015}): \frac{2014}{2015* 3^{2n+1}} [/tex]
[tex]A=2( \frac{1}{1*3}+ \frac{1}{3*5}+ \frac{1}{5*7}+...+ \frac{1}{2013*2015})* \frac{2015* 3^{2n+1}}{2014} [/tex]
[tex]A=( \frac{1}{1}-\frac{1}{3}+ \frac{1}{3}-\frac{1}{5}+ \frac{1}{5}-\frac{1}{7}+...+ \frac{1}{2013}-\frac{1}{2015})* \frac{2015* 3^{2n+1}}{2014} [/tex]
se reduc fracţii în paranteza rotundă şi rămâne:
A = [tex] (\frac{1}{1}- \frac{1}{2015}) * \frac{2015* 3^{2n+1} }{2014} [/tex]
A=[tex] \frac{2015-1}{2015}* \frac{2015* 3^{2n+1} }{2014} [/tex]
A=[tex] \frac{2014}{2015}* \frac{2015* 3^{2n+1} }{2014} [/tex]
se simplifică cu 2014 şi 2015, rămânând astfel:
A = [tex] 3^{2n+1} [/tex]